Corporate Performance and Governance in Infosys Technologies - Gupta, Sachindra Kumar (Journal of Commerce and Trade, 2011)
In the light of corporate governance practices envisaged by the recent amendments to the companies Act, 1956 and the provision of Sebi’s revised clause 49 of the Listing Agreement, this case study evaluates the quality of corporate governance practices in I.T. industry in India, particularly based on the annual report of Infosys Technologies, a leading Indian I.T. firm for the financial year 2008-2009. The study is expected to serve as a pointer to the effectiveness of current corporate governance practice in Infosys Technologies, in particular, and the Indian corporate sector, in general.